Technology investment in hospital: an empirical study. (1st September 2004) - Li, Ling; Rubin, Bruce
The purpose of this research is to investigate the relationships between technology investment at the hospital level and the effects of technology applications on hospital cost and quality performance. The relationship between technological investment and hospital cost and quality performance is empirically tested. The research suggests that technology investment is strongly related to hospital size and the number of services offered. The findings indicate that using technology to improve customer satisfaction has a significant managerial effect on hospital's quality performance. The results also suggest that patient volume is the key driver of a technology investment decision in hospitals and in alternative technology acquisition methods.